2021
DOI: 10.1016/j.xfss.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Improving embryo selection by the development of a laboratory-adapted time-lapse model

Abstract: Objective: To study whether a powerful, in-house, embryo-selection model can be developed for a specific in vitro fertilization (IVF) laboratory where embryos were already selected for transfer using general models. Design: In total, 12,944 fertilized oocytes were incubated in an EmbryoScope (Vitrolife, G€ oteborg, Sweden) at our laboratory. Embryos were selected for transfer or freezing using general models. There were 1,879 embryos with known implantation data (KID), of which 425 had positive KIDs. For the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…By using the cell division timing grouped quartiles (previously published by our group and presented in Table S1), 24 we found that fragmentation and morphokinetics were independent variables for clinical pregnancy in embryos which had up to 32% final fragmentation. We were able to show that there was no correlation between morphokinetics and degree of fragmentation up to 32% fragmentation.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…By using the cell division timing grouped quartiles (previously published by our group and presented in Table S1), 24 we found that fragmentation and morphokinetics were independent variables for clinical pregnancy in embryos which had up to 32% final fragmentation. We were able to show that there was no correlation between morphokinetics and degree of fragmentation up to 32% fragmentation.…”
Section: Resultsmentioning
confidence: 71%
“…Following embryo scoring by KIDScore D5 v.3 model, the embryos were examined also by our in‐house model 24 . For some severely fragmented embryos it was not possible to recognize all their division times and therefore to perform a full annotation.…”
Section: Tabmaterials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different quartiles represent different implantation potential. Embryos with t2 and with tSB in quartile 1 (Q1) had a higher chance to implant than embryos with t2 and tSB in quartile 4 [24]. The t2 and tSB of most of the fragmented embryos were equally distributed in the rst 3 quartiles (Table 1A) and were not concentrated in quartile 3 or 4 as one may assume.…”
Section: Resultsmentioning
confidence: 93%
“…Lately, morphokinetic time-lapse evaluation of embryos is a widespread tool used for embryo selection. We previously reported that the different morphokinetic quartiles are in correlation with clinical pregnancy and that shorter division timings yielded a signi cantly higher pregnancy rate [24]. Rhenman et al found that the degree of fragmentation is an independent signi cant predictor for success rate.…”
Section: Discussionmentioning
confidence: 93%